2020
DOI: 10.1016/j.is.2020.101534
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors contributing to the failure of information systems in public universities: The case of Iran

Abstract: In this paper, we evaluate the reasons for the failure of information systems in public universities. To that end, we start by presenting a hierarchical structure of criteria after reviewing related studies, and dividing the criteria into the categories of project management, organizational management, humanrelated, organizational and technical. To assess the weight of the criteria in the proposed framework, we collect the opinions of a sample of information technology experts working in different public unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 81 publications
1
12
1
Order By: Relevance
“…The findings of Khanfar et al (2018) and show that factors related to internal organizational problems, such as the environment, communication, requirement definition, lack of knowledge, and lack of team enthusiasm, have the greatest impact on project failure. These findings do not refute recent ERP challenges in the current study (AlBar & Hoque, 2019;Kheybari et al, 2020;Kohansal, 2019;Mahmood et al, 2019;Menon et al, 2019;Virzi, 2019).…”
Section: Erp Challengescontrasting
confidence: 93%
See 2 more Smart Citations
“…The findings of Khanfar et al (2018) and show that factors related to internal organizational problems, such as the environment, communication, requirement definition, lack of knowledge, and lack of team enthusiasm, have the greatest impact on project failure. These findings do not refute recent ERP challenges in the current study (AlBar & Hoque, 2019;Kheybari et al, 2020;Kohansal, 2019;Mahmood et al, 2019;Menon et al, 2019;Virzi, 2019).…”
Section: Erp Challengescontrasting
confidence: 93%
“…The study discovered 65 challenges, as shown in Table 4. Project management, organizational, technology & vendor, technical/architecture, employee/ personnel/ HR, people/enduser, strategic, operational/ business, management commitment, and process were the major categories identified by the reviewed papers (Ebad, 2016;Amid et al, 2012;Ganesh & Mehta, 2010a;Garg & Khurana, 2017;Khanfar et al, 2018;Kheybari et al, 2020;Mahmood et al, 2019;Sar & Garg, 2012;Tsai et al, 2005). Lack of top management support, weak BPR quality, poor IT infrastructure, insufficient user education and training, poor coordination between members of the ERP project team & organizational stakeholders, underestimated timeline and budget, low efficiency of project management, lack of IT expertise, over-reliance on heavy customization, low user engagement, lack of understanding of the need for change management, weak transfer of knowledge, misfit of the ERP system with corporate culture & structure, the resistance of users to reform, unrealistic expectations from ERP top management and unreliable data are among the top 16 critical challenges facing ERP.…”
Section: Erp Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple reasons for low transition success rates (c.f., Gaikema et al, 2019 andKheybari et al, 2020). They include algorithms that do not generalize from training to operations, use of engineering methods that cannot manage or handle the complexity of large IT projects, and failure to adapt design plans to accommodate changes in the work system's demands or mission that occur during development.…”
Section: Factors Contributing To Low Transition Successmentioning
confidence: 99%
“…Although human factors are largely responsible for GIS system failures (Madni & Jackson, 2009), lack of monitoring and evaluation equally contributes to failure (Kheybari, Rezaie, Naji, & Javdanmehr, 2020) because this phase of project implementation provides an opportunity to identify areas for improvement.…”
Section: Introductionmentioning
confidence: 99%